2020
DOI: 10.3390/ijms21082683
|View full text |Cite
|
Sign up to set email alerts
|

Modified DNA Aptamers for C-Reactive Protein and Lactate Dehydrogenase-5 with Sub-Nanomolar Affinities

Abstract: Human C-reactive protein (CRP) and lactate dehydrogenase are important markers in clinical laboratory testing—the former is used to detect in vivo inflammation, and the latter is used to detect cell necrosis and tissue destruction. We developed aptamers that bind to human CRP and human lactate dehydrogenase-5 (LDH-5) with high affinities (dissociation constants of 6.2 pM and 235 pM, respectively), applying the systematic evolution of ligands by exponential enrichment (SELEX) method, and by using a modified DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The remaining four aptamer candidates showed a lower binding affinity that was not significant, where the dissociation constants recorded were higher than 1 micromolar. Nevertheless, an aptamer can exert a higher binding affinity at the nanomolar to sub-nanomolar level against the target, according to previous reports [ 53 , 61 , 62 ]. Interestingly, negative enthalpy changes (ΔH) and entropy changes (ΔS) were recorded for both of the aptamer candidates ( Table 3 ), indicating that the Gibbs free energy may be positive or negative, depending on the temperature.…”
Section: Discussionmentioning
confidence: 82%
“…The remaining four aptamer candidates showed a lower binding affinity that was not significant, where the dissociation constants recorded were higher than 1 micromolar. Nevertheless, an aptamer can exert a higher binding affinity at the nanomolar to sub-nanomolar level against the target, according to previous reports [ 53 , 61 , 62 ]. Interestingly, negative enthalpy changes (ΔH) and entropy changes (ΔS) were recorded for both of the aptamer candidates ( Table 3 ), indicating that the Gibbs free energy may be positive or negative, depending on the temperature.…”
Section: Discussionmentioning
confidence: 82%
“…It is one of the most sensitive indicators of liver damage. LDH is an enzyme found in the cytoplasm of nearly all cells in the human body and is used to detect cell necrosis and tissue destruction [26]. One study [22] indicated that the relationship between LDH and inhospital mortality in patients with acute aortic dissection was non-linear.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Minagawa et al [ 96 ] have reported SELEX for human CRP using a pool of nucleobase-modified oligonucleotides comprised of uridine and adenine nucleotides linked to adenine and guanine nucleobases. These structurally novel constructs led to selection of a human CRP-specific aptamer having a Kd value of 6.2 pM, which reflects extraordinarily tight binding, and suggests the possibility of this aptamer being used for aptasensing of CRP with a significantly lower LOD than that mentioned above.…”
Section: Protein Detectionmentioning
confidence: 99%